Spring sea ice algal development in the sub-Arctic Ramfjorden, northern Norway - Persson, Emma (UiT Norges arktiske universitet, 2020)
The seasonal development of sea ice algae and bacteria was investigated in Ramfjorden, Norway, from February to April 2019 and compared to data from two Arctic fjords, Van Mijenfjorden and Billefjorden, sampled in April 2019. The sea ice in Ramfjorden was heavily freshwater influenced with bulk salinities ranging from 0.0 to 2.8, similar to those found in freshwater influenced Baltic Sea ice. The low bulk salinities and low brine volume fractions in combination with warm temperatures and low brine salinities resulted in a distinctly different Ramfjorden sea ice environment compared to typical marine high Arctic sea ice systems. One station in Billefjorden, located at the front of a tidewater glacier, was however similar to the sea ice environment in Ramfjorden which indicates that the freshwater input from the glacier had similar effects on the sea ice environment. Ramfjorden had a high snow depth of 10.5 to 52.5 cm during most of the time resulting in reduced light availability for algal growth. The abiotic variables combined resulted in low algal and bacterial abundances, that generally stayed two or more orders of magnitude below those from Arctic sea ice in spring. The algal community in Ramfjorden showed a seasonal succession from almost complete dominance of flagellates at the start of the ice season in February to a higher abundance of diatoms dominated by the centric diatom Leptocylindrus minimus. This succession was dependent on the age of the ice and in-ice algal growth and not defined through interactions with the phytoplankton community. Ramfjorden could in future studies be used as a model system to analyse the influence of freshwater run-off on sea ice systems and if its change will have a larger impact on high Arctic systems in the future.